The Man in the moon - Mulligan, Robert; Wingfield, Jenny; Rydell, Mark (MGM Home Entertainment Inc., 2001)
Fourteen-year-old Dani and her older sister Maureen have always shared everything. But when Court moves in next door, the sisters become rivals as Dani experience her first feelings of affection and Maureen finds the love she's longed for. But the sisters soon learn a tough life lesson when tragedy strikes and the strength of their bond is the only thing to keep their hearts from breaking.